Henry Munro - Chief of the Irish Rebels. - (:unkn) unknown (Ackermanns Gallery, 1798)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Munro, Henry; United Irishmen; Ireland -- History -- Rebellion of 1798